2000
DOI: 10.1038/82652
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic insertion upstream of Sox9 is associated with dominant XX sex reversal in the mouse

Abstract: In most mammals, male development is triggered by the transient expression of the Y-chromosome gene, Sry, which initiates a cascade of gene interactions ultimately leading to the formation of a testis from the indifferent fetal gonad. Several genes, in particular Sox9, have a crucial role in this pathway. Despite this, the direct downstream targets of Sry and the nature of the pathway itself remain to be clearly established. We report here a new dominant insertional mutation, Odsex (Ods), in which XX mice carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
232
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(244 citation statements)
references
References 30 publications
9
232
0
3
Order By: Relevance
“…Moreover, Sox9 is sufficient to trigger Sertoli cell differentiation in the embryo (Bishop et al, 2000;Vidal et al, 2001). We show here that, in ER␣␤KO ovaries, ectopic expression of Sox9 in some granulosa cells from antral follicles precedes the appearance of Sertoli cells.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, Sox9 is sufficient to trigger Sertoli cell differentiation in the embryo (Bishop et al, 2000;Vidal et al, 2001). We show here that, in ER␣␤KO ovaries, ectopic expression of Sox9 in some granulosa cells from antral follicles precedes the appearance of Sertoli cells.…”
Section: Resultsmentioning
confidence: 58%
“…Sox9 is one of the very few genes whose expression profile allows to unambiguously distinguish Sertoli and their precursors from granulosa cells: Sox9 is an early and permanent marker of the Sertoli cell lineage, as it starts to be expressed in the male genital ridge and is subsequently strongly expressed in fetal, postnatal, and adult Sertoli cells (Morais da Silva et al, 1996). In addition, its expression in the bipotent precursor for granulosa and Sertoli cells is sufficient for male sexual development during normal embryogenesis (Vidal et al, 2001;Bishop et al, 2000). It was previously shown that ER␣␤KO ovaries display an overall increase of Sox9 expression , but the ovarian cell type overexpressing the gene was not determined.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high levels of Pacrg mRNA detected in testes, we performed analyses aimed at determining both the developmental expres- sion and cellular distribution of the Pacrg transcript in this tissue. The Pacrg transcript was absent from the testes of Odd sex mutant males, which completely lack germ cells (21), suggesting that Pacrg is predominantly expressed in this cell type (data not shown).…”
Section: Pacrg Transcript Is Highly Expressed In Mouse Testesmentioning
confidence: 96%
“…2B). The stimulation of SOX9 expression was confirmed by immunoprecipitation of 35 Slabeled SOX9. Finally, we compared the basal expression of SOX9 in neonatal lightly pigmented (n-LP) skin and in neonatal darkly pigmented (n-DP) skin NHM by using immunoblotting.…”
Section: Sox9 Is Expressed In Melanocytes In Vivomentioning
confidence: 97%